Music and Emotion. Review of "Music and Emotion", monographic issue of the journal «Music Analysis», edited by Michael Spitzer, n. 29/1-2-3 (2010) - Baroni, Mario; Marconi, Luca; Pasticci, Susanna (Analitica. Rivista online di studi musicali, 2014)
The last fifteen years have seen the development of a lively interest, on an international scale, in the topic of emotion in music, documented by numerous noteworthy publications: the two volumes edited by Juslin and Sloboda [2001; 2010], the monographic issues of the journal «Musicae Scientiae» published in 2001 and 2011, and many other texts published in various parts of the world. The topic is not without repercussions also for those involved in musical analysis; and it is no mere chance that the English journal «Music Analysis» chose to dedicate the volume we are now reviewing to the subject. The contributions contained in the volume derive from an international meeting held in Durham in September 2009 and offer a fairly lively cross-section of a wide series of questions. Our only regret is that with the exception of three nordic names (Juslin, Lindström and Eerola, whose place is now solidly established in English language publications) all the authors come from the now almost self-referential context of British or American research. But of course this is nothing new.